Determination of dihydroartemisinic acid in Artemisia annua L. by gas chromatography with flame ionization detection. (18th September 2016) - Tian, Na; Tang, Yuwei; Tian, Dongming; Liu, Zhonghua; Liu, Shuoqian
Abstract: Dihydroartemisinic acid (DHAA) is the direct precursor to artemisinin, an effective anti‐malaria compound from Artemisia annua L. ( A. annua ), and it can be transformed to artemisinin without the catalysis of enzyme. A rapid and sensitive analysis of DHAA in A. annua is needed to screen excellent plant resources aimed to improve artemisinin production. In order to develop a rapid and sensitive determination method for DHAA in plant, the extraction and analysis conditions were extensively investigated in the present work. As a result, extraction of powdered A. annua leaves at 55°C for 50 min with chloroform resulted in the highest yield of DHAA, with a recovery of >98%. The precision of this gas chromatographic procedure ranged from 1.22 to 2.94% for intra‐day and from 1.69 to 4.31% for inter‐day, respectively. The accuracy was 99.55–103.02% for intra‐day and 98.86–99.98% for inter‐day, respectively. The measured LOQ and LOD values of the proposed method reached 5.00 and 2.00 μg/mL, respectively. Validation indicated the method was robust, quick, sensitive and adequate for DHAA analysis.